THE INFLUENCES OF AUDIT TENURE, SIZE OF AUDIT FIRM, AUDITOR’S EXPERTISE, NON AUDIT SERVICE AND AUDITOR’S REPUTATION TO AUDIT QUALITY (EMPIRICAL STUDY AT THE AUDIT FIRM IN MEDAN) - Baskara, Yugo (Asosiasi Dosen Akuntansi Indonesia, 2018)
The Objective of this study are to find out, analyze and prove empirically the influence of Audit Tenure, Firm Size (Public Accounting Firm), Auditor Expertise, Non Audit Services, Auditor Reputation to Audit Quality at the KAP (Public Accounting Firm) in Medan. This research is kind of causal research. The population in this study is auditor’s which has working in the public accounting firm in Medan at least 1 year. The sampling technique used was saturated sampling method with the number of respondents as many as 99 Auditor’s. The data were gathered by distributing questionnaires to each Public Accounting Firm in Medan. Method of analysis on this research by using multiple linear regression analysis. The results of this study indicate that Tenure Audit and Auditor Reputation have significantly affect on audit quality and then the Size of the Firm, Auditor Skills and Non-Audit Services have no significant effect on the Audit Quality at the Public Accounting Firm in Medan.